Properties of a thermostable nitrate reductase from the hyperthermophilic archaeon Pyrobaculum aerophilum - Afshar, S; Johnson, E; de Vries, S; Schröder, I (Journal of bacteriology, 2001)
The nitrate reductase of the hyperthermophilic archaeon Pyrobaculum aerophilum was purified 137-fold from the cytoplasmic membrane. Based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis, the enzyme complex consists of three subunits with apparent molecular weights of 130,000, 52,000, and 32,000. The enzyme contained molybdenum (0.8-mol/mol complex), iron (15.4-mol/mol complex) and cytochrome b (0.49-mol/mol complex) as cofactors. The P. aerophilum nitrate reductase distinguishes itself from nitrate reductases of mesophilic bacteria and archaea by its very high specific activity using reduced benzyl viologen as the electron donor (V(max) with nitrate, 1,162 s(-1) (326 U/mg); V(max) with chlorate, 1,348 s(-1) (378 U/mg) [assayed at 75 degrees C]). The K(m) values for nitrate and chlorate were 58 and 140 microM, respectively. Azide was a competitive inhibitor and cyanide was a noncompetitive inhibitor of the nitrate reductase activity. The temperature optimum for activity was > 95 degrees C. When incubated at 100 degrees C, the purified nitrate reductase had a half-life of 1.5 h. This study constitutes the first description of a nitrate reductase from a hyperthermophilic archaeon.